Submersed : wonder, obsession, and murder in the world of amateur submarines - Frank, Matthew Gavin (Pantheon Books, 2025)
"An exquisite, lyrical foray into the world of deep-sea divers, the obsession and madness that oceans inspire in us, and the story of submarine inventor Peter Madsen's murder of journalist Kim Wall-a captivating blend of literary prose, science writing, and true crime Submersed begins with an investigation into the beguiling subculture of DIY submersible obsessives: men and women-but mostly men-who are so compelled to sink into the deep sea that they become amateur backyard submarine-builders. Should they succeed in fashioning a craft in their garage or driveway and set sail, they do so at great personal risk-as the 2023 fatal implosion of Stockton Rush's much more highly funded submarine, Titan, proved to the world. Matthew Gavin Frank explores the origins of the human compulsion to sink to depth, from the diving bells of Aristotle and Alexander the Great to the Confederate H. L. Hunley, which became the first submersible to sink an enemy warship before itself being sunk during the Civil War. The deeper he plunges, however, the more the obsession seems to dovetail with more threatening traits. Following the grisly murder of journalist Kim Wall at the hands of eccentric entrepreneur Peter Madsen aboard his DIY midget submarine, Frank finds himself reckoning with obsession's darkest extremes. Weaving together elements of true crime, the strange history of the submarine, the mythology of the deep sea, and the physical and mental side effects of sinking to great depth, Frank attempts to get to the bottom of this niche compulsion to chase the extreme in our planet's bodies of water and in our own bodies. What he comes to discover, and interrogate, are the odd and unexpected overlaps between the unquenchable human desire to descend into deep water, and a penchant for unspeakable violence"--